Thai Consumers’ Decision to Use Electric Vehicles and the Government Policies - koojaroenprasit, sauwaluck; pumpinyo, sumaree (Universitas Mercu Buana, 2022)
Abstract This paper aimed to analyze the importance of government policies and the decision to use Electric Vehicles (EV) for Thai consumer. The paper comparing those who use Electric Vehicles to those tend to use soon. Primary data was obtained from questionnaire. The sample size was 415 comprising 224 of those who use EV and 191 of those tend to use EV soon. Methodology employed the t statistics for hypotheses testing between these two groups. The government policies in this study included import tariff reduction, special privileged for EV users and subsidy and or rebate for EV buyers. Among these government policies, both EV users and intended EV users concerned the most importance in the reduction of import tariff and for the hypothesis test showed that these two-sample group emphasized not significantly different in these policies. The policy makers should implement the reduction on import tariff as soon as possible. Keywords: government policies, EV